Semi‐Synthetic Sialic Acid Probes for Challenging the Substrate Promiscuity of Enzymes in the Sialoconjugation Pathway. Issue 23 (19th October 2020) - Mertsch, Alexander; Poschenrieder, Silvan; Fessner, Wolf‐Dieter
Abstract: A series of unusual sialic acid analogs were prepared using a semi‐synthetic strategy. Truncation of natural N ‐acetylneuraminic acid was followed by diastereoselective carbon backbone reconstruction using Barbier‐type carboligations as well as different functional group interconversions, which provided access to a variety of functional motifs in the terminal carbon backbone, including examples of saturated and unsaturated, linear and branched alkyl chains, partially deoxygenated sialic acids, sialic diacids and a first truncated legionaminic acid analog. The synthetic sialic acid probes were studied for nucleotide activation by the CMP‐sialic acid synthetase from Neisseria meningitidis using a universal pH‐shift assay for kinetic analysis. One‐pot enzymatic nucleotide activation and sialyltransfer to lactose was performed using a selection of five probes together with an engineered α2, 3‐sialyltransferase from Photobacterium phosphoreum to furnish five new‐to‐nature analogs of the GM3 trisaccharide, which were finally utilized to test the substrate tolerance of two bacterial sialidases. The obtained set of sialic acid analogs and neo‐sialocojugates provides interesting opportunities for further glycobiology studies. Abstract :